2007
DOI: 10.1002/glia.20588
|View full text |Cite
|
Sign up to set email alerts
|

Activation of CysLT receptors induces astrocyte proliferation and death after oxygen–glucose deprivation

Abstract: We recently found that 5-lipoxygenase (5-LOX) is activated to produce cysteinyl leukotrienes (CysLTs), and CysLTs may cause neuronal injury and astrocytosis through activation of CysLT(1) and CysLT(2) receptors in the brain after focal cerebral ischemia. However, the property of astrocyte responses to in vitro ischemic injury is not clear; whether 5-LOX, CysLTs, and their receptors are also involved in the responses of ischemic astrocytes remains unknown. In the present study, we performed oxygen-glucose depri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 38 publications
4
74
0
Order By: Relevance
“…However, we found that LTD 4 does not affect the proliferation of EA.hy926 cells. It has been reported that LTD 4 induces the proliferation of airway smooth muscle cells, human intestine epithelial cells, and astrocytes through activating CysLT 1 receptors; these effects are associated with airway remodeling, patho-reparation of inflammation, and glial scar formation (12,17,18,20,21,29). Nevertheless, it is also reported that LTD 4 alone can not increase the growth of bronchial fibroblasts and smooth muscle cells, but potentiates the proliferation induced by epidermal growth factor (EGF) (30,31).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, we found that LTD 4 does not affect the proliferation of EA.hy926 cells. It has been reported that LTD 4 induces the proliferation of airway smooth muscle cells, human intestine epithelial cells, and astrocytes through activating CysLT 1 receptors; these effects are associated with airway remodeling, patho-reparation of inflammation, and glial scar formation (12,17,18,20,21,29). Nevertheless, it is also reported that LTD 4 alone can not increase the growth of bronchial fibroblasts and smooth muscle cells, but potentiates the proliferation induced by epidermal growth factor (EGF) (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have recently reported distinct roles of CysLT 1 and CysLT 2 receptors in astrocytes. The CysLT 1 receptor mediates astrocyte proliferation after mild ischemic stimulation [oxygen-glucose deprivation (OGD) for 1 h] or exposure to lower concentration of LTD 4 (1 -10 nM), while the CysLT 2 receptor mediates astrocyte injury after moderate ischemia (OGD for 4 h) or exposure to higher concentration of LTD 4 (100 -1000 nM) (21). Therefore, these findings imply that CysLT 1 and CysLT 2 receptors may also play distinct roles in the endothelial responses to CysLTs; that is, CysLT 1 receptors may partially mediate angiogenesis while CysLT 2 receptors mediate inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CysLT 1 receptor regulates ischemia-induced astrocyte proliferation and glial scar formation as well [27,28] . However, how AQP4 deficiency impacts the expression and localization of CysLT 1 and CysLT 2 receptors remains unknown.…”
Section: Introductionmentioning
confidence: 99%